Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence